The Land and People of Afghanistan - Clifford, Mary Louise (Philadelphia J. B. Lippincott, 1973)
An introduction to the history, geography, people, and culture of this landlocked country of central Asia, with special sections on recent political, economic, educational and social reforms.
Include Index, Colour Illustration and Maps
Keywords: Afghanistan